Factors of Selecting and Publishing News of Gatekeepers in Tishreen and Al-Watan Newspapers (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed at examining the influential factors in selecting news of gatekeepers in Tishreen and Al-Watan, the Syrian Newspapers, as well as exploring the distribution of gatekeepers roles in these newspapers by making the final decision for publication, and identifying their perception of news and validity criteria for selection and publishing, The study used the method of media survey through in-depth interview tool with 15 gatekeepers in Tishreen Newspapers, and seven in Al-Watan Newspaper in 2016. The study results showed that news values,business ethics, political power, editorial policy and the ownership were the most significant factors in selecting news. Editor in chief plays an essential role in the series of final decision to publish in these newspapers, while editors are fullfilling a limited role. The study recommended to train journalists in their various administrative levels about the latest developments in news industry (selection, preparation, drafting, publishing), making the biggest field for editors to participate in selection news, editing, publishing, and placement news that meet criteria for publishing but Don’t suit newspapers trends in other media arts. The study called for comparative studies about gatekeepers roles between the Syrian, Arab and foreign media to see variation in local contexts of each country, expansion in understanding of gatekeepers roles by connecting the gatekeeping theroy with other media theories.